2016
DOI: 10.31964/jkl.v13i1.30
|View full text |Cite
|
Sign up to set email alerts
|

Tingkat Kebisingan Di Kawasan Permukiman Sekitar PLTD Muara Teweh

Abstract: Level of Noise in the residential around muara teweh’s PLTD. Muara Teweh’s PLTD was one of the regional companied responsible for the provision of electricity serviced. The impact of the operation of the PLTD is the emergence of noise caused by the PLTD engine so that it appeared on public complainted, especially communication disordered, disordered of physiological and psychological disordered. This study aims to determine the noise level and subjective complainted felt in residential areas around Muara Teweh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…The results of respondent's responses based on the questionnaire showed that all respondents felt that the sound generated by the SGP2 Project was noisy, as many as 77% of respondents experienced psychological disorders that were disturbed or uncomfortable in their activities, as many as of respondents experienced physiological disorders in the form of insomnia, and as many as 77% of respondents wanted the noise around their home decrease. These results are consistent with the results of the study "Tingkat Kebisingan di Kawasan Permukiman Sekitar PLTD Muara Teweh" i.e respondents exposed to noise ≤70 dB(A) were mostly uncomfortable and had difficulty sleeping (Hasanah and Maharso, 2016). In this study, there are other findings data that most of the respondents complained about the dust was increasing at their houses, so that some respondents were suffering from diseases generated by dust, including ISPA, cough, and DHF.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The results of respondent's responses based on the questionnaire showed that all respondents felt that the sound generated by the SGP2 Project was noisy, as many as 77% of respondents experienced psychological disorders that were disturbed or uncomfortable in their activities, as many as of respondents experienced physiological disorders in the form of insomnia, and as many as 77% of respondents wanted the noise around their home decrease. These results are consistent with the results of the study "Tingkat Kebisingan di Kawasan Permukiman Sekitar PLTD Muara Teweh" i.e respondents exposed to noise ≤70 dB(A) were mostly uncomfortable and had difficulty sleeping (Hasanah and Maharso, 2016). In this study, there are other findings data that most of the respondents complained about the dust was increasing at their houses, so that some respondents were suffering from diseases generated by dust, including ISPA, cough, and DHF.…”
Section: Resultssupporting
confidence: 90%
“…In a previous study, entitled Tingkat Kebisingan di Kawasan Permukiman Sekitar PLTD Muara Teweh discusses the influence of noise on the activities of people in settlements bordering the PLTD Muara Teweh (Hasanah and Maharso, 2016). But in this study discusses the effect of noise on the activities of people in settlements bordering the building construction project.…”
Section: Introductionmentioning
confidence: 83%
“…Selain itu kebisingan pun dapat menimbulkan gangguan pada aktivitas di lingkungan masyarakat seperti masalah komunikasi, fisiologi maupun psikologi. Gangguan komunikasi yang sering terjadi yaitu berbicara lebih keras, sedangkan untuk gangguan fisiologi yang sering dirasakan yaitu sakit kepala dan gangguan psikologi terbanyak adalah respon merasa tidak nyaman akibat suara bising yang ditimbulkan [6] serta kebisingan juga dapat menimbulkan masalah sosial [7]. Benturan antara alat kerja, pekerjaan bekisting, pengecoran, lalu lintas konstruksi serta penggunaan alat-alat berat merupakan beberapa sumber kebisingan dari kegiatan konstruksi tersebut.…”
Section: Pendahuluanunclassified
“…48 tahun 1996 tentang baku tingkat bising. (Uswatun Hasanah, Zulfikar Ali As, 2016) Berdasarkan observasi lapangan yang telah dilakukan sebelumnya di Lokasi PLTD Labasiano terletak dikawasan pemukiman masyarakat,dan jalan raya padat/ramai.khususnya di jam sibuk kendaraan yaitu pagi,siang dan sore hari. Kendaraan yang melintas dan bunyi Mesin PLTD dapat menimbulkan suara bising yang memungkinkan terganggunya masyarakat yang beraktifitas terlebihnya PLTD labasiano itu sangat terganggu dengan pelayanan kesehatan (puskesmas) sehungga perlu dilakukan pengukuran tingkat kebisingan di lingkungan kawasan industri.dengan demikian DLH dapat menjadikan hasil penelitian ini sebagai bahan pertimbangan dalam mengambil kebijakan lingkungan di daerah kerjanya.…”
Section: Pendahuluanunclassified